The Effect of a Proposed High- Intensity Training Program on the Body Composition of Males (25 to 35 years- old) Participating in Fitness Centers in Palestine - Awwad, Abed Alsamad Saleh; Kaid, Mahmoud Wajh; Nassib, Sabri; Souissi, Nizar (Journal of Educational and Psychological Sciences, 2021)
The study aims at identifying the effect of high intensity training program on some physical and mobile variables and on body structure among males aged between 25- 35 years participating in physical fitness centers in Palestine.The experimental method has been used by choosing a random sample of 48 individuals distributed on 30 centers in Palestine. High intensity training program has been designed, and contains ten standardized exercises for the study sample.The present findings showed significant differences in all physical and mobile variables in addition to body structure, except for the variable of muscle mass. These differences were in favor of the posttest. Moreover, significant differences appeared in the variable of water mass and in favor of the pre- test, despite it was a reverse result.In light of the study results, several recommendations have been suggested, the most important of which is adopting high intensity training program in order to improve some physical, mobile variables and body structure in the body building centers for its importance in saving time and improving the physical and mobile variables and body structure.
Keywords: High intensity; Training program; Body fitness; Body structure